NIPK, a protein pseudokinase that interacts with the C subunit of the transcription factor NF-Y, is involved in rhizobial infection and nodule organogenesis - Clúa, Joaquín; Rípodas, Carolina; Roda, Carla; Battaglia, Marina E.; Zanetti, María Eugenia; Blanco, Flavio Antonio (Frontiers in Plant Science, 2022)
Heterotrimeric Nuclear Factor Y (NF-Y) transcription factors are key regulators of the symbiotic program that controls rhizobial infection and nodule organogenesis. Using a yeast-two hybrid screening we identified a putative protein kinase of Phaseolus vulgaris that interacts with the C subunit of the NF-Y complex. Physical interaction between NIPK (for NF-YC1 Interacting Protein Kinase) and NF-YC1 occurs in the cytoplasm and the plasma membrane. Only one of the three canonical amino acids predicted to be required for catalytic activity is conserved in NIPK and its putative homologs from lycophytes to angiosperms, indicating that NIPK is an evolutionary conserved pseudokinase. Postranscriptional silencing on NIPK affected infection and nodule organogenesis, suggesting NIPK is a positive regulator of the NF-Y transcriptional complex. In addition, NIPK is required for activation of cell cycle genes and early symbiotic genes in response to rhizobia, including NF-YA1 and NF-YC1. However, strain preference in co-inoculation experiments was not affected by NIPK silencing, suggesting that some functions of the NF-Y complex are independent of NIPK. Our work adds a new component associated with the NF-Y transcriptional regulators in the context of nitrogen-fixing symbiosis.